Economic impact: river conservation at Sungai Dobi by using vegetative buffer zone / Mohd Shahnom Ismail … [et al.] - Ismail, Mohd Shahnom; Ashari, Jeffri; Rosley, Effy Farissa; Zainil Abidin, Nur'Ainaa; Abd Razak, Maizatul Akmar; Maskor, Nur Afiqah; Md Taib, Norraeffa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
River pollution, flash flood, soil erosion, shallow river are among the problem face by the authorities that led to highly maintenance cost to conserve the river. By comparing approaches done by America, Britain and Taiwan, this research going to prove that vegetative buffer zone along the river will give a greater positive impact towards the economy society and ecosystem. Vegetative Buffer Zone will protect the soil erosion, stimulate native organism to growth, attract tourist, cleaner water, source and greener environment. Species of plants to be planted are decided according to the type of soils and its optimum potential economic impact.